(untitled) (Nepal Medical College Journal, 2020)
The main objective of the study was to see the association of dyslipidemia in preeclampsia (PET) as compare to normotensive (NT) patients. It was a descriptive study done in Nepal Medical College Teaching Hospital Department of Obstetrics and Gynecology from April 2019 from April 2020. A total of 75 PET (test group) and 75 NT (control group) in their third trimester were included. Their fasting lipid profile was studied. It was found that triglyceride (TG) and very low density lipoprotein (VLDL) was significantly high among PET group as compared to that of NT patients. The mean TG of PET group was 266.11± 98.61 and the NT group was 187±58.56 (p=0.00) and the mean VLDL of PET group was 46.00±15.31 and NT group was 37.88±12.85 (p=0.001). On the other hand, the total cholesterol (TC), low density lipoprotein (LDL) and high density lipoprotein (HDL) were not significantly different in both the groups. It was also found that with the severity of the disease (Preeclampsia), the level of TG and VLDL increased significantly. Therefore, among the investigation done for PET, we should include lipid profile, especially the TG and VLDL. Furthermore, TG and VLDL should be measured serially (at least once a week) so as to predict the progress of PET and manage the patient accordingly.